Toward a General Model for the Description of Multimedia Clinical Data - Ferri, F.; Pisanelli, D. M.; Ricci, F. L.; Consorti, F.; Piermattei, A. (Methods of Information in Medicine, 1998)
The patient folder integrates information originating from heterogeneous sources. For this reason computerized tools for patient data management should exploit the advantages of multimediality and offer an integrated environment for data presentation, and image and biosignal visualization. Object-oriented modeling is the best approach for designing systems for multimedia patient folder management.We propose an object-oriented model, able to define the entities constituting the patient folder and their logical organization. This model has sufficient flexibility to adapt to the most varied clinical environments. It allows the physician to structure the information needed for his/her patient folder without employing a programming language.
Keywords: Patient Folder; Data Model; Multimedia Systems; Databases